Kecerdasan Buatan Dalam Perspektif Agama Islam - Mubarak, Roy; Widya Lelisa Armi; Oman Fathurohman SW (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2025)
This study aims to explore the ontology of artificial intelligence (AI), specifically exploring its philosophical and theological underpinnings and their implications for the concept of faith in Islam. Adopting a descriptive qualitative approach and library research, the paper draws on primary sources, including the Qur'an (e.g., QS. Al-Mujadalah 11, Al-Jasiyah 13, Al-'Alaq 1-5) and Hadith, to establish a theological foundation. Secondary data comprises contemporary scientific journal articles on AI in Islam from a non-figh perspective, focusing on the integration of AI with Islamic ethical principles for education and community empowerment. The analysis reveals that AI is viewed as an outcome of Allah SWT's gift of reason ('aql), aligning with the Islamic spirit of seeking knowledge and the embodiment of taskhir (the submission of the universe to humanity). AI has significant potential to enhance the accessibility of Islamic education. However, its adoption necessitates a strong Islamic ethical framework, guided by the principles of Maqāṣid al-Sharī‘ah (the objectives of the Shari'a), to ensure fairness, non-discrimination, and harm prevention. The study concludes with several key implications: the Islamic education curriculum should be reformed to include the subject "Fiqh of Technology," and there is a critical need for collective ijtihad among technology scholars. Furthermore, developing Sharia Compliance Audit Standards (SAKS) for AI systems is crucial, along with encouraging Muslims to transition from technology consumers to producers, to ethically guide AI's future practical implementation